Oxygen delivery at high blood viscosity and decreased arterial oxygen content to brains of conscious rats - Rebel, Annette; Lenz, Christian; Krieter, Heinrich; Waschke, Klaus F.; Ackern, Klaus van; Kuschinsky, Wolfgang (American journal of physiology. Heart and circulatory physiology, 2001)
We addressed the question to which extent cerebral blood flow (CBF) is maintained when, in addition to a high blood viscosity (Bvis) arterial oxygen content (CaO2) is gradually decreased. CaO2 was decreased by hemodilution to hematocrits (Hct) of 30, 22, 19, and 15% in two groups. One group received blood replacement (BR) only and served as the control. The second group received an additional high viscosity solution of polyvinylpyrrolidone (BR/PVP). Bvis was reduced in the BR group and was doubled in the BR/PVP. Despite different Bvis, CBF did not differ between BR and BR/PVP rats at Hct values of 30 and 22%, indicating a complete vascular compensation of the increased Bvis at decreased CaO2. At an Hct of 19%, local cerebral blood flow (LCBF) in some brain structures was lower in BR/PVP rats than in BR rats. At the lowest Hct of 15%, LCBF of 15 brain structures and mean CBF were reduced in BR/PVP. The resulting decrease in cerebral oxygen delivery in the BR/PVP group indicates a global loss of vascular compensation. We concluded that vasodilating mechanisms compensated for Bvis increases thereby maintaining constant cerebral oxygen delivery. Compensatory mechanisms were exhausted at a Hct of 19% and lower as indicated by the reduction of CBF and cerebral oxygen delivery.